Issues in the design of technology and projects for livestock producers in Africa - Okali, C. (Departmento de Difusao de Tecnologia, 1987)
Highlights the relationship between types of technology and the involvement of different categories of producers in the Development process. Emphasizes the need to base improvements or changes on existing systems where small livestock/farm systems are the focus. Suggests that non-governmental organizations (NGOs) might have a role to play in facilitating communication between researchers and farmers. Adresses channels for improving communications to adress the wider policy framework.